Coordination as a Mechanism for Implementing the Concept of Multi-Level Governance in Ukraine - Suvorov, Valentin (Theory and Practice of Public Administration, 2023)
The article examines the essence and features of coordination as a mechanism for implementing the concept of multi-level governance, the definition of methodological approaches to the use of methods and means of horizontal and vertical coordination in the system of multi-level governance in Ukraine. It was found that the complex mechanism of coordination in the multi-level management system is based on the applied aspect of the hierarchy of coordination goals and involves the use of a number of methods and means of achieving its goals based on the principles of coordination, which should include: interconnection and simultaneity, hierarchical subordination, coordination, balance, balance, redundancy, unity of commands and actions, etc. At the same time, the methods and means of coordination can be such as: visa and other forms of mutual control, distribution of tasks according to the management hierarchy, creation of committees and commissions, meetings between departments, dissemination of information, negotiations, direct observation, development of rules, procedures, schedules, norms, plans, etc. On the basis of research concerning coordination mechanisms in complex hierarchical systems, it was determined that the triune coordination system is based on: restrictions - narrowing of the set of known connections, which includes: instructions (norms) and standardization (sets of standard operations); informing - expansion of the set of known connections, which includes: vertical and horizontal communications using the entire set of available information and forms of communications; purely coordination - it is based on a balance between narrowing and expanding a set of known connections, which allows you to use reference information and focus it on the performance of certain tasks (from the decomposition of the general task) in order to fulfill certain indicators (criteria) with the help of both standard operations and and other forms of communications. Using the process and project approach in establishing effective coordination, the process of algorithmization and the demonstration of a step-by-step algorithm for solving complex problems to the subjects of program implementation and project executors with the receipt of feedback from this link in the form of finding out how much is quite important tasks are adequate from the point of view of coordination with executors in conditions of multitasking regarding priorities, availability of resources, deadlines, etc. At the same time, a condition for solving complex problems with the help of establishing an effective coordination system is their decomposition into appropriate sub-tasks and the selection of adequate methods and means of their solution in the specified time. It is proven that the improvement of the complex mechanism of coordination between all subjects of institutional interaction is an important component of solving practical problems of multi-level management. As for the role of the coordinator, who is a key subject of the hierarchical system responsible for coordinating the activities of various decision-making centers, he should emphasize and focus not on the current state of the coordination objects of the lower level, but on specific, primarily intermediate results of their work , determined in the form of certain indicators at the corresponding stages of the implementation of programs and projects for a clear period of time. This will make it possible to increase the effectiveness of coordination and make reasoned decisions related to the choice of the current coordinating action depending on the tactical situation in conditions of uncertainty.